Use of digital technological resources by faculties from two higher education institutions in Brazil - Paula, Rejane Sales de Lima [UNESP]; Casarin, Helen de Castro Silva [UNESP]; de Almeida, Cátia Cândida; Lucas, Margarida (Universidad Nacional de La Plata, 2023)
This article presents the results on the use of digital resources by higher education professors from two Brazilian public institutions from area 2 of DigCompEdu. This is a descriptive-inferential study that aims to verify how teachers have selected and used digital resources in their classes; identify how they have been creating and modifying the contents necessary for teaching; check how these professors have been protecting students' personal data. For data collection, the online Check-In DigCompEdu questionnaire, version 2021, adapted to the context of Brazilian higher education, was used, which was applied through the Limesurvey platform. 224 teachers participated in this study. As a result, it was found that 28% of the participants have used search engines and internet platforms and 27.5% have evaluated and selected the resources according to the students' needs, however, 2.2% of the professors indicated not knowing use the Internet for research. 27.7% of teachers have created their own digital presentations, but say they don't know how to do much more than that. 8.5% said they were not concerned with the protection of personal data, as they believe that the university should take care of this issue. It was concluded that it is necessary to improve teachers' skills to use digital resources more effectively and safely in their academic activities. It was recommend that university libraries play a more effective role in the development of actions that promote the digital competence of teachers.
Uso de recursos digitales por profesores de dos instituciones de educación superior en Brasil
Uso dos recursos tecnológicos digitais por professores de duas instituições de ensino superior no Brasil
Keywords: Brazil; DigCompEdu; Digital literacy; Digital resources; Faculty; Teaching mediated by technologies